2014
DOI: 10.7314/apjcp.2014.15.19.8069
|View full text |Cite
|
Sign up to set email alerts
|

Crosstalk between EGFR and p53 in Hepatocellular Carcinoma

Abstract: Background: Hepatocellular carcinoma (HCC) is one of the most frequent cancers worldwide, with a high mortality. Most patients present with late stage disease, when the treatment options are limited to systemic chemotherapy. The purpose of our study was to evaluate the significance of p53 and EGFR expression in HCC, and to determine whether these two markers correlate with conventional parameters of prognosis. Materials and Methods: Our study included a total of 45 patients, diagnosed histopathologically with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 30 publications
0
5
0
Order By: Relevance
“…Studies have already suggested that nm23 with pro-oncogenic potential was involved in hepatocarcinogenesis [ 31 ], and that its expression in tumor tissues was correlated with metastasis and survival in HCC, which may also be an indicator for prognosis [ 32 ]. Studies also showed that overexpression of p53 contributed to the hepatocarcinogenesis and more advanced stage of HCC [ 33 ]. As we found there was significant difference of miR-193a-3p expression in nm23 as well as p53-positive and -negative HCC patients in the current study, miR-193a-3p may be a pro-oncogenic potential indicator, as nm23 and p53 are in HCC.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have already suggested that nm23 with pro-oncogenic potential was involved in hepatocarcinogenesis [ 31 ], and that its expression in tumor tissues was correlated with metastasis and survival in HCC, which may also be an indicator for prognosis [ 32 ]. Studies also showed that overexpression of p53 contributed to the hepatocarcinogenesis and more advanced stage of HCC [ 33 ]. As we found there was significant difference of miR-193a-3p expression in nm23 as well as p53-positive and -negative HCC patients in the current study, miR-193a-3p may be a pro-oncogenic potential indicator, as nm23 and p53 are in HCC.…”
Section: Discussionmentioning
confidence: 99%
“…HCC patients manifest conspicuously elevated levels of vascular endothelial growth factor (VEGF) expression and frequently show increased co-expression of TGF-alpha and EGFR [8], leading to active and massive cell proliferation because TGF-alpha, epidermal growth factor receptor (EGFR) and its ligand EGF play important roles in cell proliferation [9]. Erlotinib, a tyrosine kinase inhibitor that down-regulates VEGF, was reported to be efficacious in advanced HCC [10, 11].…”
Section: Introductionmentioning
confidence: 99%
“…Other clinical studies evaluated the co-expression of mutant p53 and EGFR mutations/overexpression in different tumours, suggesting a correlation with poor prognosis and a lack of response to tyrosine kinase inhibitors, chemotherapy and radiotherapy in non-small cell lung cancer, head and neck, and hepatocellular malignancies [81][82][83][84]. However, the clinical role of TP53 mutational status in CRC is still controversial.…”
Section: Discussionmentioning
confidence: 99%